Clinical And Pathogenetic Significance Of Endogenous Intoxication In Children With Acute Pneumonia (Global Scientific Review, 2023)
For quite a long time, various aspects of the diagnosis and prognosis of pneumonia in young children continue to be an urgent problem clinical pediatrics. So, according to WHO, this pathology is one of the main causes of infant and child mortality. Pneumonia kills more than million children, which corresponds to a figure of 17.5% in the structure death of children under 5 years of age. For clinicians and researchers, the problem of an increase in the number of complicated forms of pneumonia among young children remains relevant. The main reason, according to most authors, is the deterioration of the state of resistance of children in modern conditions, as a result of a pronounced intoxication syndrome, which is the more pronounced, the younger the child. The study of peripheral blood is the most reliable mediator of children's health assessment.